The study of relationship between the production volume of natural rubber, the wages of estate workers and the production volume of synthetic rubber towards the price of the natural rubber / Wan Nur Hadaniah Wan Mohd Kamal - Wan Mohd Kamal, Wan Nur Hadaniah (Faculty of Business and Management, 2006)
The purpose of the study is to identify whether the production volume of natural rubber. the wages of estate worker and the production volume of synthetic rubber has a positive or negative relationship with or could be the factor to determine the price of natural rubber The data is collected on monthly basis taken from January 2000 until October 2005 This study used Simple and Multiple Regression Model to analyse the three variables concerned From the result, it is shown that the production volume of natural rubber and production volume of synthetic rubber have significant relationship With the price of natural rubber. Then the wages of estate worker has no significant relationship with price of natural rubber The production volume of synthetic rubber shows the strongest relationship compare to other variables.